What Radiologist Should Know about MRI Translational Forces and Hazard: An Ex-Vivo Simulation of Retained Metallic Shrapnel - Ali Kanj; Ibrahim Ghosn; Assaad Mohanna; Georges Rouhana (Radiology Research and Practice)
Background. In a country immersed in endless rounds of wars, retained metallic foreign bodies remain a significant dilemma in the daily practice of every Lebanese radiologist. When a shrapnel’s hazard is of concern, the decision between performing or refusing a justified MRI exam is not always straightforward. In this small trial, we aimed to better understand the shrapnel’s MRI safety by mimicking our daily practice. Methods. Five shrapnel with an incremental increase in their long axis were put in an animal flesh and then introduced into a 3 T magnetic field. The behavior of each shrapnel was concretely assessed by performing before and after magnetic field exposure CT acquisitions. Results. Translation along the z-axis ranged from 0.9 mm to 2.8 mm. Torque angle ranged between 2.8 and 54 degrees with an average of 15.62 degrees. Conclusions. Shrapnel’s movements in the magnetic field are not negligible during the acute phase of injury where there is no reinforcing fibroblastic reaction and invite us to reconsider the MRI safety of these metallic foreign bodies. Standard radiographs may be sufficient, but a targeted CT scan may be of better value for a confident decision for assessment of shrapnel position near viscera and major vessels.